CLASSROOM INTERACTION PATTERNS ANALYSIS IN ENGLISH CLASSES OF PHARMACY DEPARTMENT - Rahardini, Nimas Ayu (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study aims to investigate the classroom interactions that occur in the English class of the Pharmacy study program at Universitas Kadiri using the IRF model and investigates how the implementation of tasks based on TBLT stimulate student engagement. The researcher conducted observations in the English class of the Pharmacy study program at Universitas Kadiri. As a passive observer, the researcher collected data by recording video and audio and taking notes during the teaching and learning process. This study is descriptive qualitative research that explores or describes social situations related to student engagement in English classes of non-English major students in depth. The results showed that the use of a sequence of tasks in this class helped to increase student interaction and engagement in the learning process. Implementing types of collaborative tasks has a positive impact on improving classroom interaction. The lecturer also initiated the interaction to help them understand the task process according to the sequence and rules. In addition, the study strongly recommends the role of lecturer as a facilitator in organizing and facilitating the learning process specifically in the process of students completing tasks.